The impact of emotional intelligence on problem behaviour among adolescents in Malaysia - Yap, Ming Hui; Koh, Doh Hian; Yap, Chin Choo *; Tan, Soon Aun; Gan, Su Wan (Future Academy, 2019)
Juvenile offences are on the rise over the recent years and have led to serious societal concern in Malaysia. Thus, this study was designed to investigate the relationship of both interpersonal and intrapersonal emotional intelligence relating to problem behaviours among adolescents in Malaysia. A quantitative research design method and cross-sectional research design was selected as our main data collection method to obtain data from different age groups and demography status of populations at same period. By using multistage cluster sampling method, 600 school-going adolescents from Penang, Perak and Johor were recruited and 496 sets of questionnaires were completed. The age of the participants ranged from 13 to 17 (m = 15.07, SD = 1.08). Profile of Emotional (PEC) scale and Strength and Difficulties Questionnaire (SDQ) were used as the instruments to assess the variables understudy. The results showed that both intrapersonal and interpersonal emotional intelligence were negatively correlated with problem behaviours. Furthermore, multiple regression analysis revealed that intrapersonal emotional intelligence is the only significant predictor in explaining adolescents’ problem behaviours. This research provides empirical support to the importance of intrapersonal emotional intelligence in discouraging adolescents from developing problem behaviours.